A POTENSIAL EKONOMI HUTAN MANGROVE DI PERCUT SEI TUAN: POTENSIAL EKONOMI HUTAN MANGROVE DI PERCUT SEI TUAN - Rahmawati, Rahmawati; Nuraida; Iriadi, Ridwan; Hanum, Erlia (Program Studi Magister Pengelolaan Sumberdaya Alam dan Lingkungan Universitas Almuslim, 2025)
This study assessed the potential of the mangrove forest ecosystem in Percut Sei Tuan, Deli Serdang Regency, North Sumatera, with the aim of evaluating the biodiversity, ecological function, and economic potential of the mangrove forest. The research was conducted through field surveys, vegetation inventory, and interviews with 30 local people. The results showed that the mangrove forest area in Percut Sei Tuan has high species diversity with seven main mangrove species. The ecological functions of mangroves as coastal protection, pollutant filters, and living places for coastal fauna are also clearly identified. In addition, the results of this study show great economic potential, which can be utilized sustainably, through activities such as ecotourism, fish farming, and non-timber forest product management. This study recommends the need for community-based management that takes into account conservation aspects and sustainable development of the local economy